Hydrological Study of Sahibi River Basin in Alwar District (1970-2020), With Major Emphasis on Groundwater Depletion, Rainfall Fluctuation and Population Increase: Assessment of Rainfall Fluctuation, Groundwater Depletion, and Population Increase in Sahibi River Basin (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water is one of the most valuable natural resource. It plays an important role in the well–being and development of human society. Throughout the human history, we witnessed that man and water has been closely associated with each other as many of the supreme civilizations of ancient world were scattered along bank of rivers for example - Mesopotamia along Tirgis and Euphrates river Chinese civilization along yellow river, Indus valley civilization etc. A river is a natural flowing water resource usually fresh water, river Basin is considered as the basic hydrological unit from planning and development of water resources. The recycling process of water on earth is called Hydrological cycle or “the water cycle”. This cycle plays a key role in maintaining dynamic equation of water on earth. Fresh water can only be replenished through the process of water cycle, in which water from seas, lakes, forests, lands, rivers etc. evaporates, form cloud and returns as precipitations. Nowadays due to various problems such as global warming, population increase, or urbanization etc. hydrological cycle of earth is disturbed which results in high water scarcity .Worldwide ground water is continuously depleting due to excessive human use. Due to sporadic occurrence of rainfall, recharge system is badly affected. The main aim of this paper is to assess the level of rain fall fluctuation and ground water depletion of Sahibi river basin alonwith population increase affecting recharge system, in Alwar district over last 30 year and the causes related.